Does Auditor Industry Expertise Improve Audit Quality In Complex Business Environments? - Sansaloni Butar-Butar; Stefani Lily Indarto Lily Indarto (Institute of Research and Community Outreach - Petra Christian University, 2018)
This study examines the role of specialist auditors in enhancing the quality of financial statements by taking into account industry complexity. The test of hypotheses are conducted in two steps. The first step is to provide evidence that earnings quality, measured by earnings persistent, of firms operating in the complex and non-complex industry are different. The second step is to compare the absolute abnormal accruals of companies engaged in the complex industry with those from non-complex industry audited by non-specialist and specialists auditors. Results show: 1) earnings persistence of firms in complex industries are lower than those in non-complex industries. 2) absolute abnormal accruals of firms operating in complex industries are higher than those in non-complex industries regardless industry specialization. Overall, the results suggest that auditor industry expertise does not play a significant role in improving the quality of audited earnings in complex business environment.